Toxicity and antipyretic effect of hibiscus rosa-sinensis L. and hibiscus rosa-sinensis var. alba flower and leaf ethanol extracts rats - Abdul Aziz, Muhammad Wahizul Haswan (2013)
Hibiscus rosa-sinensis has been traditionally used by local communities to treat fever. However, there are only limited data have been published to support the antipyretic effects. The objective of this study is to investigate the antipyretic properties and possible mechanism of the ethanol extracts of Hibiscus rosa-sinensis L. (red) and Hibiscus rosa-sinensis var. Alba (white) flower and leaf. Phytochemical analysis, heavy metals screening and acute toxicity test were done to evaluate the safety of extracts. The first model ran induced fever in rats by injecting Brewer's Yeast subcutaneously and then treated with 4 extracts at dosage 5 & 50 mg/kg. The dosages used for the study were obtained by the acute toxicity test. Ibuprofen was used as a reference drug, with dose 100 mg/kg. The results of the study showed that white flower extract 5 mg/kg and 50 mg/kg significantly (p<0.05) reduced the total temperature when compared to positive control group. For the second model, 50 mg/kg dosage was chosen based on the first model. The rats were induced to fever by injecting 100 μg/kg lipopolysaccharide (LPS) intraperitoneally. LPS model is divided into pre-treatment and post-treatment studies. Pre-treatment was done with ethanol extract treated prior to fever induced by LPS whereas post-treatment will be induced by LPS, and then treated with the extracts. Temperatures of rats were measured using a digital thermometer. The results were expressed as mean ± S.E.M. and analyzed using the SAS system. In pre-treatment, the ethanol extract of H. rosa-sinensis (red) flower indicate a significant impediment of temperature rise (p<0.05) in rectal temperature when compared to control at all times. In post-treatment, statistical analysis revealed that only H. rosa-sinensis (red) flower ethanol extract of have significant (p<0.05) antipyretic effect in abolishing the LPS-induced fever in rats and the values were comparable to Ibuprofen. Similarly, the H. rosa-sinensis (red) flower extract showed more potency than ibuprofen at the first and second hour, but less potent at third hour until the fifth hour. The data showed that both extracts of H. rosa-sinensis var. Alba (white) flowers and H. rosa-sinensis (red) flowers have antipyretic property on pyrexia models. To determine the correlation of Prostaglandin E2 (PGE2) in the physiology of fever, peripheral blood of rats was taken and the serum was measured for PGE2 metabolite content. The results of the pre-treatment study showed extracts of H. rosa-sinensis var. Alba (white) flower 50 mg/kg have significantly lower PGE2 (1.43 ± 0.64 pg/ml) than control (4.03 ± 0.07 pg/ml). For post-treatment, Ibuprofen, H. rosa-sinensis (red) flower and H. rosa-sinensis var. Alba (white) flower 50 mg/kg extracts showed significant (p>0.05) decrease of PGE2 when compared to control. Therefore, this research suggest the probability for its therapeutic effectiveness as plant-based antipyretic agent as claimed by traditional medicine practitioners of our local community.